DESKRIPSI RENCANA PELAKSANAAN PEMBELAJARAN DAN BAHAN AJAR TEMATIK KELAS VI SEKOLAH DASAR - Yusnita Etty; Siti Halidjah; Dyoty Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the thematic learning tools 2013 curriculum theme 1sub-theme 1 class VI semester 1 State Elementary School 15South Pontianak whichrefers to the regulation of the minister of education andculture in circular letternumber 14 of 2019 regarding simplificationlesson plan. The research method usedisdescriptive method with a qualitative approach. The things that are describedarecompleteness of the learning implementation plan (RPP) and alignment ofteaching materialswith the 2013 curriculum thematic learning implementation plantheme 1sub-theme 1 grade VI Elementary School 15 South Pontianak. Datasourcein this study obtained from the sixth grade teacher of State ElementarySchool 15South Pontianak. The data from this research is in the form of animplementation plan documentthematic learning, teaching materials and theresults of interviews and questionnaires. TechniqueData analysis used in thisresearch is Miles and Hubermen.To test the credibility of the data on the results ofthis study, thenused triangulation of data collection techniques, namely bychecking the data the same source with different techniques.Keywords: Description, Lesson Plan, Teaching Materials, Thematic Learning